E-cadherin to N-cadherin switching in the TGF-β1 mediated retinal pigment epithelial to mesenchymal transition. (July 2022) - Wei, Jiayi; Wu, Liangjing; Yang, Shuai; Zhang, Conghui; Feng, Le; Wang, Minli; Li, Hui; Wang, Fang
Abstract: A serious form of ocular fibrotic disease is proliferative vitreoretinopathy (PVR) that can ultimately lead to blindness. While the pathogenesis of PVR is known to be closely tied to retinal pigment epithelial (RPE) cell epithelial-mesenchymal transition (EMT) characterized by E-cadherin downregulation and N-cadherin upregulation. Herein, we developed a model of transforming growth factor-β1 (TGF-β1)-induced EMT using human RPE (hRPE) cells as a tool for exploring the mechanistic basis for E-cadherin to N-cadherin switching. This analysis revealed that the loss of E-cadherin led to the separation of β-catenin from the catenin-cadherin complex whereupon it underwent nuclear entry to activate zinc finger E-box binding homeobox 1 (ZEB1), in turn promoting N-cadherin upregulation in this biological context. E-cadherin overexpression was sufficient to inhibit this EMT process and proliferation in RPE cells, further constraining their TGF-β1-induced apoptosis. Highlights: The switching from E-cadherin to N-cadherin in EMT of RPE cells plays a pivotal role in PVR. β-catenin and ZEB1 play a crucial role in the switching from E-cadherin to N-cadherin. Expression of E-cadherin could significantly inhibit RPE cells EMT, cell proliferation and apoptosis induced by TGF-β1.